Rapid induction of antigen-specific CD4 + T cells is associated with coordinated humoral and cellular immunity to SARS-CoV-2 mRNA vaccination - Painter, Mark M; Mathew, Divij; Goel, Rishi R; Apostolidis, Sokratis A; Pattekar, Ajinkya; Kuthuru, Oliva; Baxter, Amy E; Herati, Ramin S; Oldridge, Derek A; Gouma, Sigrid; Hicks, Philip; Dysinger, Sarah; et al. (Immunity (Cambridge, Mass.), 2021)
SARS-CoV-2 mRNA vaccines have shown remarkable clinical efficacy, but questions remain about the nature and kinetics of T cell priming. We performed longitudinal antigen-specific T cell analyses on healthy SARS-CoV-2-naive and recovered individuals prior to and following mRNA prime and boost vaccination. Vaccination induced rapid antigen-specific CD4 T cell responses in naive subjects after the first dose, whereas CD8 T cell responses developed gradually and were variable in magnitude. Vaccine-induced Th1 and Tfh cell responses following the first dose correlated with post-boost CD8 T cells and neutralizing antibodies, respectively. Integrated analysis revealed coordinated immune responses with distinct trajectories in SARS-CoV-2-naive and recovered individuals. Last, whereas booster vaccination improved T cell responses in SARS-CoV-2-naive subjects, the second dose had little effect in SARS-CoV-2-recovered individuals. These findings highlight the role of rapidly primed CD4 T cells in coordinating responses to the second vaccine dose in SARS-CoV-2-naive individuals.